Animal Swear Words in Compliments on X: A Pragmatic Study - Putri, Aprilia Kartika; Fitriah, Siti; Triandana, Anggi; Amri, Ulil; Putra, Yoga Mestika (Jurnal Sastra Indonesia, 2024)
Few people know that swear words are not always used to express anger. They can also be used to express positive emotions, such as compliments. The phenomenon of using swear words in compliments was found on one social media, X, formerly known as Twitter. This study aims to analyze the pragmatic meanings and pragmatic functions of animal swear words in English compliments on social media X. This study is descriptive research with a qualitative approach. The data were collected by observing the animal swear words-contained tweets on X. The data were analyzed by using the distributional method (the basic technique and either one of the seven extended techniques: deletion, substitution, extension, insertion, reversion, transformation, and repetition) and the identity method by referring to the theories of Hughes (2006), Ljung (2010), Kreidler (2008) , and Spears (2000). The results of the study showed that the word bitch ('female dog'; ’unpleasant woman’) was the only swear word used in compliments. The pragmatic meaning of the swear word is an utterance, meaning 'girl' or ‘guy.’ Meanwhile, the practical functions of the swear word in compliments are as an anaphoric use of epithets and noun supports. This study is expected to reduce misunderstandings among Indonesian EFL (English as a Foreign Language) students when communicating with other English speakers on social media X.